He was some kind of a man : masculinities in the B western - McGillis, Roderick (Waterloo, ON : Wilfrid Laurier University Press, 2009)
He Was Some Kind of a Man: Masculinities in the B Western explores the construction and representation of masculinity in low-budget western movies made from the 1930s to the early 1950s. These films contained some of the mid-twentieth-century's most familiar names, especially for youngsters: cowboys such as Roy Rogers, Hopalong Cassidy, and Red Ryder. The first serious study of a body of films that was central to the youth of two generations, He Was Some Kind of a Man combines the author's childhood fascination with this genre with an interdisciplinary scholarly exploration of the films influ.
Contents; Preface; 1 Introduction: Ride the High Country, or "They Went Thataway"; 2 Cowboy Codes: Straight and Pure and All Boy; 3 When We Were Young: Nostalgia and the Cowboy Hero; 4 Arms and the Man: The Friendly Gun; 5 Give Me My Boots and Saddles: Camp Cowboy; 6 Tall in the Saddle: Romance on the Range; 7 White Hats and White Heroes: Who Is That Other Guy?; 8 Virgin Land: Landscape, Nature, and Masculinity; 9 Corporate Cowboys and the Shaping of a Nation; Postscript: The Frontiersman (1938); List of Films Mentioned; References; Index.
Includes bibliographical references and index.
Print version record.
ForeWord Magazine Book of the Year Awards (nominated), 2009
eBooks on EBSCOhost
Keywords: Masculinity in motion pictures; Western films -- History and criticism; Masculinité au cinéma.; Westerns -- Histoire et critique; PERFORMING ARTS -- Film & Video -- Reference; Performing Arts; Masculinity in motion pictures; Western films; Cowboy; Geschlechterrolle; Männlichkeit; Western; USA; Film; Westernfilm; USA; Criticism, interpretation, etc